A Bibliometric Analysis of Virtual Reality in Anatomy Teaching Between 1999 and 2022 - Li, Zhuoshu; Li, Zixin; Peng, Cheng; Zhao, Mingyi; He, Qingnan (Frontiers in Education, 2022)
Human anatomy is an important medical subject that includes abstract content and strong operability. The lack of specimens required for anatomical experimental teaching and unclear observation of fine structures of specimens lead to difficulties for students in learning. As a new technology in the field of computers, virtual reality (VR) has been widely used in the medical field and has great development potential and application value. Its use in the teaching of human anatomy has received increasing attention. This technology increases the sense of reality of medical students in learning and improves the learning effect, including initiative and enthusiasm of students. Publications were obtained from the Web of Science (WoS) Core Collection on April 30, 2022, with the following retrieval strategy: [(TS = VR) OR (TS = virtual reality)] AND (TS = anatomy) AND [(TS = education) OR (TS = train*) OR (TS = teach*) OR (TS = learn*) OR (TS = study*)] NOT TS = (surgery), and the time frame was from 1999 to 2022. Then, VOSviewer software, Excel and GraphPad Prism 9 were used to analyze the data. The keywords included cocitations, countries/territories, publication numbers, institutions, authors and journals of publications. A series of scientometric and visualized analyses were conducted, and a table for a detailed analysis of the application of VR in anatomy teaching was created. This paper mainly analyses the application status and progress of VR technology in anatomy teaching, which is shown to improve the anatomical learning effect of medical students. In conclusion, the application of VR technology in human anatomy has great potential.